World around you. English reading : (NNAW^ALXNIJ POS)QÆBNIK(B.s)E Pt. III, An academic year and holidey in a countryside - (NdZ@BA(B, (Nw(B. (Nk(B.,s ((NhARK)QÆW (B:s)E (NrANOK(B, (NwESTA(B,s, 2002)
(NnAW^ALXNIJ POS)QÆBNIK QWLQÃ SOBO@ SERÆ@ UROKÆW(B, (NNAPRAWLENIH NA ROZWITOK NAWI^OK USNOGO MONOLOGÆ^NOGO TA DÆALOGÆ^NOGO MOWLENNQ TA ROZ[IRENNQ SLOWNIKOWOGO ZAPASU U^NÆW NA BAZÆ ^ITANNQ TEKSTÆW PRO VITTQ U wELIKOBRITANÆÇ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NmOWOZNAWSTWOs -- (NaNGL)QÆJSXKA MOWAs)E